A note on the k-domination number of a graph - Y. Caro; Y. Roditty (International Journal of Mathematics and Mathematical Sciences)
The k-domination number of a graph G=G(V,E), γk(G), is the least cardinality of a set X⊂V such that any vertex in VX is adjacent to at least k vertices of X.